Hyalinizing epithelioid tumors with OGT‐FOXO fusions. A case report of a non‐acral soft tissue mass harboring a novel FOXO4 gene rearrangement. Issue 7 (2nd February 2021) - Torrence, Dianne; Zhang, Lei; Sung, Yun‐Shao; Dickson, Brendan C.; Antonescu, Cristina R.
Abstract: Recurrent fusions between OGT and members of the Forkhead box (FOXO) family of genes have been recently described in three cases of hyalinizing epithelioid acral soft tissue tumors in young adults showing co‐expression for EMA and CD34. Despite the lack of an established myoepithelial lineage by immunohistochemistry, these lesions have been labeled as myoepithelioma‐like due to their epithelioid phenotype and sclerotic background. In this study, we report a novel FOXO4‐OGT fusion identified by targeted RNA sequencing in an unclassified shoulder soft tissue mass in a 40‐year‐old male. The tumor showed nodular foci of increased cellularity in a uniformly hyalinized background. The neoplastic cells were mainly epithelioid and focally spindled, with eosinophilic cytoplasm and indented nuclei with mild atypia. The tumor lacked significant mitotic activity and necrosis. Immunohistochemically, the tumor showed variable positivity for EMA, pan‐CK, CD34, ERG and FLI1, while it was negative for CD31, S100, SOX10, desmin, and MUC4. INI1 expression was retained. Due to its unusual histology and conflicting immunoprofile, TruSight RNA fusion panel sequencing was performed which revealed a fusion between FOXO4 exon 2 to OGT exon 2. This is the first example of a soft tissue lesion harboring OGT ‐related fusions occurring in a non‐acral location and associated with FOXO4 gene. Its line of differentiation and biologic potential remain uncertain.